Top-Down Proteomics of Human Saliva Highlights Anti-inflammatory, Antioxidant, and Antimicrobial Defense Responses in Alzheimer Disease - Contini, Cristina; Olianas, Alessandra; Serrao, Simone; Deriu, Carla; Iavarone, Federica; Boroumand, Mozhgan; Bizzarro, Alessandra; Lauria, Alessandra; Faa, Gavino; Castagnola, Massimo; Messana, Irene; Manconi, Barbara; et al. (Frontiers in Neuroscience, 2021)
Alzheimer disease is the most prevalent neurodegenerative disease in the elderly, characterized by accumulation in the brain of misfolded proteins, inflammation and oxidative damage leading to neuronal cell death. By considering the viewpoint that Alzheimer disease onset and worsening may be influenced by environmental factors causing infection, oxidative stress, and inflammatory reaction, we investigated the changes of the salivary proteome in a population of patients with respect to that one of healthy controls. Indeed, the possible use of saliva as a diagnostic tool has been explored in several oral and systemic diseases. Moreover, the oral cavity continuously established adaptative and protective processes toward exogenous stimuli. In the present study, quali/quantitative variations of fifty-six salivary proteoforms, including post-translationally modified derivatives, have been analyzed by RP-HPLC-ESI-IT-MS and MS/MS analysis, and immunological methods were applied to validate MS results. The salivary protein profile of Alzheimer disease patients was characterized by significant higher levels of some multifaceted proteins and peptides either specific of the oral cavity or also expressed in other body districts: i) peptides involved in the homeostasis of the oral cavity; ii) proteins acting as ROS/RNS scavengers and with a neuroprotective role, such as S100A8, A9 and their glutathionylated and nitrosylated proteoforms, cystatin B and glutathionylated and dimeric derivatives; iii) proteins with antimicrobial activity, such as α-defensins, cystatins A and B, histatin 1, statherin and thymosin β4, this last with neuroprotective role at level of microglia. These results suggested that, in response to injured conditions, Alzheimer patients established defensive mechanisms detectable at oral level.